Cancer in Youth Living With HIV (YLWHIV): A Narrative Review of the Access to Oncological Services Among YLWHIV and the Role of Economic Strengthening in Child Health - Katumba, Ruth G. N.; Sensoy Bahar, Ozge; Johnson, Kimberly J.; Ssewamala, Fred M. (Frontiers in Public Health, 2020)
Youth Living with HIV/AIDS (YLWHIV) have a higher risk of developing immunodeficiency related illnesses including certain cancers than their general population counterparts of the same age. This narrative review of current available literature describes factors associated with pediatric access to oncological services, and the role economic strengthening could play in improving health outcomes for this vulnerable population. Findings suggest that both HIV-infected and -uninfected children living in low and middle-income countries struggle with access and adherence to cancer treatment and care. Cost of treatment is a major barrier to access and adherence. Asset-building savings programs may increase financial security and subsequently result in better health outcomes although they have not been utilized to improve access to cancer treatment.